Pharmacokinetics of isoniazid in Wistar rats exposed to ethanol - Taísa Busaranho Franchin; Jonata Augusto de Oliveira; Caroline Damico Candido; Evelin dos Santos Martins; Elias Carvalho Padilha; Michel Leandro de Campos; Rosângela Gonçalves Peccinini (Universidade de São Paulo, 2023)
Abstract Tuberculosis treatment consists of a drug combination, where isoniazid is the core drug and alcoholism is a factor highly related to poor patient compliance with the therapy. CYP2E1 is an enzyme involved both in the metabolism of ethanol and in the formation of hepatotoxic compounds during the metabolism of isoniazid. The shared metabolism pathway accounts for the possibility of pharmacokinetic interaction in cases of concomitant alcohol use during tuberculosis treatment. The aim of this study was to evaluate the effect of repeated exposure of Wistar rats (males, 250 g, n=6) to ethanol on the pharmacokinetics of a single dose of isoniazid in combination with pyrazinamide and rifampicin (100 mg/kg, 350 mg/kg and 100 mg/kg, respectively). An animal group received the combination of drugs and ethanol and was compared to a control group, which received the combination of drugs without exposure to ethanol. The plasma concentrations of isoniazid were determined by a UHPLC/UV bioanalytical method that was previously validated. Biochemical markers of liver function were measured to assess potential damage. A lower elimination half-life of isoniazid was observed in the ethanol group than in the control group (t1/2 0.91 h versus 1.34 h). There was no evidence of hepatotoxicity through the biomarker enzymes evaluated. The results allow us to infer that although there are no biochemical changes related to liver damage, there is a slight influence of ethanol exposure on the pharmacokinetic profile of isoniazid. This change may have a relevant impact on the efficacy of isoniazid in the outcome of tuberculosis treatment.